The general’s intuition : overconfidence, pattern matching, and the inchon landing decision - Vennesson, Pascal (2019)
Can we trust the operational intuitions of generals? The proponents of the overconfidence model, one of the most influential perspectives in the psychology of judgment, commonly offer a skeptical answer. Generals’ operational intuitions are likely to be hampered by overconfidence and negatively affect military effectiveness. However, the successful operational outcome of General Douglas MacArthur’s decision to land at Inchon (June–September 1950) seemingly contradicts the model. We seek to complement and refine the overconfidence model by examining the Inchon landing decision through the analytical lens of the recognition-primed decision model. This model typically envisions that under specific circumstances—notably an experienced decision maker, an adequate environment regularity, and an opportunity to learn—generals are able to make quick and satisfactory decisions. We show that such a configuration was present in the Inchon landing case and helps explain both the decision process and its successful outcome.